2000
DOI: 10.1159/000052042
|View full text |Cite
|
Sign up to set email alerts
|

International Variations in Youth Drug Use: The Effect of Individual Behaviours, Peer and Family Influences, and Geographical Location

Abstract: This international study investigates factors underlying international variations in rates of youth drug use among representative samples of 15-year-olds in five cities (Bremen, n = 871; Dublin, n = 983; Groningen, n = 487; Newcastle upon Tyne, n = 880; Rome, n = 666). It reveals a higher level of drug use in English-speaking compared to continental populations. Drug use was associated with peer, family and individual factors. Logistic regression showed that family structure and sport were associated with lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…National and international studies have shown that low rates of drug use are associated with traditional family structure [13,14]. We did not find this association.…”
Section: Comparison With Other Studiescontrasting
confidence: 82%
“…National and international studies have shown that low rates of drug use are associated with traditional family structure [13,14]. We did not find this association.…”
Section: Comparison With Other Studiescontrasting
confidence: 82%
“…Several studies (1,7,8,29) indicated that sport practice was associated with lower rates of drug use and Peretti-Watel et al (30) described that it was less frequent that elite athletes used tobacco, alcohol and cannabis, although it depended on the type of sport practiced and the level of competition. Several studies (1,7,8,29) indicated that sport practice was associated with lower rates of drug use and Peretti-Watel et al (30) described that it was less frequent that elite athletes used tobacco, alcohol and cannabis, although it depended on the type of sport practiced and the level of competition.…”
Section: Discussionmentioning
confidence: 99%
“…Participating in sports is believed to be protective against drug abuse [2, 3]. Nevertheless, the prevalence of drug abuse among athletes of different disciplines has prompted many researchers over the years to probe into the whys and the wherefores of this phenomenon [4, 5].…”
Section: Introductionmentioning
confidence: 99%